The Effect of the Foundation Subject to the Final Year Subject - K., Kadirgama; M. M., Noor; M. S. M., Sani; R. A., Bakar; A., Ibrahim (2009)
This paper discussed the foundation or pre-requisite subjects influence the student’s performance in Heat Transfer subject in University Malaysia Pahang (UMP) and its importance to achieve Outcome Based Education (OBE). Thermodynamics I and II are prerequisite subject for Heat Transfer. Randomly 30 mechanical engineering students were picked to analysis their performance. Regression analysis and Neural Network were used to prove the effect of pre-requisite subject toward Heat transfer. The analysis shows that Thermodynamics I highly affect the performance of Heat transfer and the students who excellent in Thermodynamics I, will achieve excellent performance in Thermodynamics II and Heat transfer. This result shows that excellent foundations on early years will effect to the final year result directly.